The Effect of Organizational Culture Dimensions on the Internal Service Quality for Internal Customers in Benghazi Children’s Hospital. - خالد د. مريم محمد حسن; الكيخيا د. فيصل سالم; عبد اللطيف أ. سرور عبد الكريم (Dirasat in Economics and Business, 2021)
This study aimed to test the effect of organizational culture dimensions on the internal serv-ice quality for internal Cust-omers in Benghazi Children’s Hospital, and to find out which dimensions have the greatest im-pact. It also aimed to identify the differences of Customers views about study variables (organizat-ional culture, internal service quality) according to demograp-hic variables (gender, age group, academic qualification, years of experience, current job). To ac-hieve this goal, a survey que-stionnaire was used, through a stratified sample of (278) ind-ividual clients. A set of appropriate statistical methods were used test hypo-thesis. The results of the study indicated that there is a positive significant impact of organizat-ional culture on internal service quality. The results also revealed that the supportive culture in the organizational environment has the strongest influence on int-ernal service quality, and the study also found that there were there was no difference in opi-nions between sample units for the study variables (organizati-onal culture and internal service quality) according to demograp-hic variables (gender, Age gro-up, academic qualification, years of experience, current job). Ba-sed on the results, the study introduced recommendations th-at may contribute to benefit from the organizational culture in enhancing the level of internal service quality.